2021
DOI: 10.3390/ani11020341
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Characteristics and In Vitro Digestibility of Fibers and Fiber-Rich Byproducts Used for the Feeding of Pigs

Abstract: Dietary fibers may have positive impact on health and wellbeing of pigs. The study examined physicochemical properties of two lignocelluloses (including and excluding bark), powdered cellulose, Aspergillus niger mycelium, lucerne chaff, soybean shells, wheat bran, and sugar beet pulp in relation to fermentability and digestibility using in vitro batch-culture incubation. Maize starch and a purified cellulose were used as standardized substrates for classification of the test substrates. The substrates covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The higher production of gas in B1 and B2 diets may be due to higher content of fermentable nutrients and easily digestible fibre. However, cumulative gas production (ml/0.5g feed) in in-vitro fermentation was less compared to experiments of Youssef and Kamphues, (2020) who used substrate without enzymatic hydrolysis; but results were comparable to that reported by Bachmann et al (2021) for fibre rich ingredients like sugar beet pulp, soybean shell, lucerne and wheat bran after pre-digestion with enzymes. This may be due to the fact that predigested substrate mostly produces less gas, NH 3 and short chain fatty acids as compared to substrate without pre-digestion (Bachmann et al, 2021).…”
Section: Cumulative Gas Production During Fermentationsupporting
confidence: 45%
“…The higher production of gas in B1 and B2 diets may be due to higher content of fermentable nutrients and easily digestible fibre. However, cumulative gas production (ml/0.5g feed) in in-vitro fermentation was less compared to experiments of Youssef and Kamphues, (2020) who used substrate without enzymatic hydrolysis; but results were comparable to that reported by Bachmann et al (2021) for fibre rich ingredients like sugar beet pulp, soybean shell, lucerne and wheat bran after pre-digestion with enzymes. This may be due to the fact that predigested substrate mostly produces less gas, NH 3 and short chain fatty acids as compared to substrate without pre-digestion (Bachmann et al, 2021).…”
Section: Cumulative Gas Production During Fermentationsupporting
confidence: 45%
“…Thus, it is reasonable to conclude that the e cient utilization of cellulose, as well as xylan, arabinoxylan and βglucan, is important for the e cient utilization of dietary ber overall when feeding DT pigs a diet with wheat bran as the main ber source. Pigs do not secrete enzymes that degrade ber, but they can ferment ber under the action of intestinal microorganisms that produce organic acids (Bachmann et al, 2021). In this study, we found that the content of organic acids in the feces of DT pigs was signi cantly higher than that of DLY pigs under the same feeding conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, it coincides with increased production of SCFA, generating additional fuel for large intestinal enterocytes and cell proliferation ( Scheppach, 1994 ). Further study is needed to identify the cause of the more proximal shift in fermentation site due to grass hay, but it is well-studied that cellulose-rich material on itself is poorly fermentable in pigs ( Bachmann et al., 2021 ), especially young individuals. Hence, the likely explanation for the fermentation shift is an effect of the grass hay on the passage of the fermentable fractions of the ingested creep feed and milk oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%